Designing English Language Teaching Materials For Tourism Based on Project-Based Learning for English Education Study Program Students - Serasi, Reko; Arono, Arono; Yunita, Wisma (Journal of Education Research, 2024)
This study aims to develop English language teaching materials based on the Project-Based Learning (PBL) learning model for English for Tourism course. This study used a research and development (R&D) with the ADDIE model whose stages consist of analysis, design, development, implementation, and evaluation. Participants in this study were 5th semester students majoring in English Language Education at one of the state Islamic universities in Bengkulu. Data collection techniques used observation, interviews, and questionnaires. The prototype of the development of teaching materials was validated by experts in content, language and design. Then, the teaching materials were tested on individual, small group, and large group. The results of the validation of teaching materials had an overall average value of 81.9%. Meanwhile, the overall trial of teaching materials found a value of 78%. Then, the results of interviews and project assessments showed that the developed teaching materials increased student motivation and competence in learning. The conclusion is that the development of teaching materials based on Project-Based Learning is qualified as good and suitable to use in the classroom learning process.